Evaluating financial risk with investment guidelines - Kornmann, Lauren (Kansas State University, 2014)
Cash management practices for corporate treasurers are in a state of instability in recent years. Events during the credit crisis of 2008 have had an impact on how organization’s cash positions are managed. This has led corporate treasurers to juggle unprecedented amounts of cash across multiple bank counterparties and invest these funds based on previous investment policies with potentially inflexible limits. Many regulations have been passed to strengthen domestic and global financial systems, yet the risk of default is not completely removed and there are many uncertain ties that corporates face. To succeed in the uncertain financial environment, counterparty risk tools must be put in place to improve the visibility of potential operational risk, along with a higher frequency of reviewing and updating investment policies. It is crucial for corporates to look beyond the traditional market perceptions and bank credit ratings to evaluate counterparty risk. Although these continue to be a valuable metric, they should be incorporated with other forward looking market risk metrics such as credit default swaps, capital and asset resiliency metrics, and growth and profitability metrics to their current investment guidelines review. By integrating risk metrics to help formulate an investment policy, corporates can adapt to the changing financial environment. This thesis examined methodologies to develop a more accurate and immediate viewpoint of counterparty creditworthiness. This was done through the creation of models using market information to set values to view the strength of counterparties and the likelihood of default. Models were created for both financial institutions and countries where cash or investments are placed. Depending on the models, this restricts the permissible investment options that an institution or country has. This approach allows the company to invest more with higher rated counterparties, and sets a maximum to those who are deemed high risk of default. The findings of this thesis identified that it is crucial to classify the right metrics and look beyond traditional market perceptions and bank credit ratings. By implementing a balanced process that regularly monitors current market indicators of counterparty risk, an organization will be in a stronger position to define and determine the potential risk. This creates a balanced view of both backward looking and forward looking metrics such as long term debt ratings and credit default swaps. These metrics were useful indicators of a counterparty’s strength. Because of the wide range of information available and cost, it went beyond the resources of the company to perform detailed ongoing analysis. It was also identified that a risk-adjusted approach to setting counterparty limits is crucial for managing counterparty exposure and the risk of default. To optimize liquidity, it is in the company’s best interest to place higher balances in institutions with the lowest risk of default. Grouping banks into tiers and assigning a percentage of total balance to each tier allows for financial institutions to have a specific limit capacity. Incorporating these tools on a frequent basis allows for real-time analysis of counterparty exposure and risk.
Keywords: Portfolio; Credit risk; Finance; Counterpart risk